Method for measuring granularity of graphite in crystalline flake graphite ore

Through the combined method of static acid leaching, ultrasonic acid leaching and vacuuming and pressurized acid leaching treatment, the problem of inaccurate graphite particle size determination in the prior art is solved, and the acquisition of high-purity graphite products and accurate graphite particle size determination are achieved.

CN119666676APending Publication Date: 2025-03-21CNBM RESEARCH INSTITUTE FOR ADVANCED GLASS MATERIALS GROUP CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510170929.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-17
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art has deviations in determining the graphite particle size in flake graphite ore, especially when the gangue content in graphite ore is high, it is difficult for conventional acid mixing methods to completely dissolve the gangite minerals, resulting in inaccurate determination of graphite particle size.

Method used

The combination of static acid leaching treatment, ultrasonic acid leaching treatment and vacuuming and pressurized acid leaching treatment is adopted to gradually remove gangue minerals in graphite ore, increase the fixed carbon content of graphite products, and thus accurately determine the graphite particle size.

Benefits of technology

This method can obtain high-purity graphite products while maintaining graphite integrity, which significantly improves the accuracy of graphite particle size determination.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides a method for measuring the granularity of graphite in crystalline flake graphite ore, which comprises the following steps of: drying and crushing graphite ore, sequentially carrying out static acid leaching treatment, ultrasonic acid leaching treatment, vacuumizing and pressurized acid leaching treatment, washing to be neutral, carrying out suction filtration, and drying to finally obtain a high-purity graphite product, the granularity of the graphite in the crystalline flake graphite ore can be accurately determined by standard screening. The method has the advantages that the steps are simple, the operation is convenient, the high-purity graphite product can be obtained on the premise of maintaining the integrity of the graphite, and the graphite granularity in the crystalline flake graphite ore can be accurately measured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of mineral content determination in mineral processing, in particular to a method for determining graphite particle size in flake graphite ore. Background Art

[0002] Crystalline graphite has a unique crystal structure and excellent physical and chemical properties, and is an irreplaceable raw material in emerging fields. Graphite is divided into crystalline graphite (flake graphite) and cryptocrystalline graphite according to different crystal forms, among which crystalline graphite is further divided into flake graphite and vein graphite. Flake graphite can usually be divided into large flake graphite (+100 mesh) and fine flake graphite (-100 mesh) according to the size of the flakes. Compared with fine flake graphite, large flake graphite has a wider range of applications and higher economic value. Therefore, the content of large flake graphite in natural flake graphite ore is an important indicator for judging the value of graphite ore.

[0003] At present, the determination of graphite particle size characteristics is mostly done by grinding light slices and thin slices and then using line measurement method under a microscope to statistically analyze the graphite intercalation particle size characteristics. This method will lead to certain deviations in the statistical results due to factors such as graphite flake aggregation and graphite and gangue mineral intercalation. Therefore, a method that can more accurately determine the graphite particle size characteristics in flake graphite ore is needed.

[0004] CN105823712A discloses a method for determining the content of large flake graphite in flake graphite ore. The method uses thermal cracking to achieve preliminary dissociation of graphite and gangue minerals, adds mixed acid, stirs, and stands to dissolve the gangue minerals to obtain graphite flake products. However, the gangue in some graphite ores has a high silicon content, and it is difficult to dissolve all the gangue minerals by conventional mixed acid methods, resulting in a low fixed carbon content in the final graphite product, and it is difficult to accurately determine the graphite particle size characteristics. Summary of the invention

[0005] The present invention is to overcome the deficiencies in the prior art and provide a method for measuring the particle size of graphite in flake graphite ore.

[0006] This application provides the following technical solutions: A method for determining the particle size of graphite in flake graphite ore, characterized in that it comprises the following steps: (1) Select graphite ore and put it into an oven for drying; (2) Using a crusher to break the dried graphite ore into particles smaller than 6 mm; (3) subjecting the crushed graphite ore to static acid leaching treatment; In step (3), the specific process of the static acid leaching treatment is: placing the crushed graphite ore into a polytetrafluoroethylene beaker, adding a mixed acid, standing and soaking for 24 hours at room temperature and pressure, removing the upper clear liquid, and repeating 2 to 4 times; (4) Wash the graphite ore after static acid leaching until it is neutral, filter it and dry it, and then perform ultrasonic acid leaching treatment; In step (4), the specific process of the ultrasonic acid leaching treatment is: washing the graphite ore after room temperature acid leaching until it is neutral, filtering, and drying, placing it in a stainless steel ultrasonic device coated with polytetrafluoroethylene with heating and stirring functions, adding mixed acid, stirring at 40-80°C for 2-6 hours, standing and settling, removing the upper clear liquid, and repeating 1-4 times; (5) Wash the graphite ore after ultrasonic acid leaching to neutrality and dry it, and then perform vacuum leaching followed by pressurized acid leaching; In step (5), the specific process of the vacuum-first followed by pressurized acid leaching treatment is as follows: the graphite ore after ultrasonic acid leaching is washed with water until it is neutral and dried, large particles of gangue minerals are visually searched and removed, and then the graphite ore is placed in a device under a vacuum degree of -0.06 to -0.08 MPa, mixed acid is added, stirred evenly, heated to 45 to 70°C under a pressure of 0.04 to 0.08 MPa, and stirred for 2 to 4 hours to obtain a mixed solution; (6) The mixed solution is washed with water until it is neutral, filtered, and dried to obtain high-purity flake graphite, which is then sieved using a standard sieve to determine the graphite particle size.

[0007] On the basis of the above technical solutions, there are also the following further technical solutions: The drying equipment in step (1) is an oven, and the oven is set at a temperature of 100-105°C.

[0008] The mixed acid in steps (3), (4) and (5) refers to an acid solution obtained by mixing hydrofluoric acid, hydrochloric acid and nitric acid. The volume ratio of hydrofluoric acid to hydrochloric acid is (1-4): (1-3): (1-3), and the liquid-solid ratio of the mixed acid to graphite is 0.8-5.5 ml / g.

[0009] The ultrasonic operating frequency in step (4) is 28~40kHz.

[0010] The equipment described in step (5) is a reactor, which is connected to a vacuum pump, a stirring device and a sample injection bottle. The inner wall of the reactor and the stirring device are both made of polytetrafluoroethylene material. The graphite ore dried after ultrasonic acid leaching is placed in the reactor, and the mixed acid solution is added to the sample injection bottle. Before adding the mixed acid, the graphite ore needs to be placed in a vacuum degree of -0.06~-0.08MPa for 10~50min.

[0011] Advantages of the invention: The method for determining the particle size of graphite in flake graphite ore provided by the present invention has simple steps and is easy to operate. Under the premise of maintaining the integrity of graphite, a high-purity graphite product can be obtained and the particle size of graphite in flake graphite ore can be accurately determined.

[0012] In the method provided by the present invention, the gangue minerals in the graphite ore can be preliminarily removed by static acid leaching treatment; the ultrasonic acid leaching treatment can utilize the strong shock waves and micro jets generated by ultrasonic waves to scrub the mineral surface, increase the frequency and speed of the movement of material molecules, accelerate the continuous reaction and contact between the mixed acid and the gangue minerals, and further remove most of the gangue minerals in the graphite ore; and the acid leaching treatment by vacuuming first and then pressurizing is beneficial to the discharge of gas in the mineral pores and the infiltration of the mixed acid, so as to promote the reaction of the mixed acid with the gangue minerals in the pores of the graphite ore, increase the fixed carbon content of the graphite product, and accurately determine the graphite particle size in the flake graphite ore. DETAILED DESCRIPTION Example

[0013] The flake graphite ore produced in Madagascar was selected, with a fixed carbon content of 6.88% and main gangue minerals of quartz, mica, pyrite, chlorite, feldspar and kaolinite. The flake graphite ore was put into an oven for drying, weighed 268.55g, and crushed to 5 mm by a crusher.

[0014] Then put the crushed graphite ore into a polytetrafluoroethylene beaker, place it in a ventilated place, add 700 ml of mixed acid into the beaker, the mixed acid is prepared by mixing hydrofluoric acid, hydrochloric acid and nitric acid in a volume ratio of 3:2:1.

[0015] Soak for 24 hours at room temperature and pressure, and then remove the supernatant. Add 600 ml of mixed acid, soak for 24 hours at room temperature and pressure, and remove the supernatant. Add 500 ml of mixed acid, soak for 24 hours at room temperature and pressure, and remove the supernatant. Wash the minerals with water until neutral, filter and dry, then place the minerals in an ultrasonic device, add 250 ml of mixed acid, heat to 65°C, stir for 4 hours, the ultrasonic working frequency is 28 kHz, let stand for 30 minutes and pour out the supernatant; add 180 ml of mixed acid, heat to 70°C, stir for 3 hours, the ultrasonic working frequency is 28 kHz, and let stand for 30 minutes. After pouring out the upper clear liquid, the obtained lower mixed liquid was washed with water to neutrality, filtered, and dried in turn. After removing large particles of gangue minerals with the naked eye, it was placed in a reactor, 75 ml of mixed acid was added to the sample bottle, and the vacuum degree was pumped to -0.06Mpa. After maintaining for 15 minutes, the vacuum pump was turned off, the valve of the sample bottle was opened, and the mixed acid was flowed into the reactor by pressure difference. The valve of the sample bottle was closed, and after stirring evenly, the pressure was applied to 0.06Mpa, heated to 55°C, and stirred for 3 hours to obtain a mixed liquid. The mixed liquid was washed with water to neutrality, filtered, and dried in turn, and then 18.37g of high-purity flake graphite was obtained, and the fixed carbon content of the graphite product was 99.20%.

[0016] After sieving the graphite product through 30 mesh, 50 mesh, 80 mesh, 100 mesh and 200 mesh standard sieves for 15 minutes in turn, it was measured that the +30 mesh flake graphite in the graphite ore accounted for 1.98%, the -30 mesh + 50 mesh flake graphite accounted for 39.32%, the -50 mesh + 80 mesh flake graphite accounted for 22.16%, the -80 mesh + 100 mesh flake graphite accounted for 11.12%, the -100 mesh + 200 mesh flake graphite accounted for 20.88%, and the -200 mesh flake graphite accounted for 4.54%.

[0017] Comparative Example 1 using prior art: The same flake graphite ore produced in Madagascar was selected, with a fixed carbon content of 6.88%. The main gangue minerals are quartz, mica, pyrite, chlorite, feldspar, and kaolinite. The graphite ore was put into an oven for drying, weighed 250.72g, put into a high-temperature resistance furnace with nitrogen, heated to 700°C, calcined for 10 minutes, taken out and quickly immersed in water, taken out and hammered to less than 6 mm, put into a polytetrafluoroethylene beaker after oven drying, placed in a ventilated place, added 700ml of mixed acid (hydrofluoric acid: hydrochloric acid: nitric acid = 3:2:1), heated to 65°C, stirred for 4h, let stand for 30 minutes and pour out the supernatant; then add 500m l mixed acid, heated to 70℃, stirred for 3h, allowed to stand for 30 minutes, and poured out the supernatant; then added 400ml mixed acid, heated to 70℃, stirred for 3h, allowed to stand for 30 minutes, and poured out the supernatant, and then the lower mixed liquid was sieved to remove large particles of gangue minerals with the naked eye to obtain 17.36g of graphite product with a fixed carbon content of 83.88%. After sieving with a 100-mesh standard sieve for 15 minutes, it was measured that the +100-mesh product accounted for 77.35% of the graphite product. Example

[0018] The flake graphite ore produced in Heilongjiang was selected, with a fixed carbon content of 7.85%, and the main gangue minerals are quartz, feldspar, mica, calcite, kyanite, pyrite, and amphibole. The flake graphite ore was put into an oven for drying, weighed 298.5g, and crushed to 5.5 mm by a crusher.

[0019] Then put the crushed graphite ore into a polytetrafluoroethylene beaker, place it in a ventilated place, and add 800 ml of mixed acid, which is a mixture of hydrofluoric acid, hydrochloric acid and nitric acid in a volume ratio of 3:2:2.

[0020] At room temperature and pressure, let it stand and soak for 24 hours, remove the supernatant; then add 700ml of mixed acid, let it stand and soak for 24 hours at room temperature and pressure, remove the supernatant; then add 550ml of mixed acid, let it stand and soak for 24 hours at room temperature and pressure, remove the supernatant, wash the lower mixed liquid with water until it is neutral, filter it, and dry it, place it in an ultrasonic device, add 300ml of mixed acid, heat it to 70℃, stir it for 5 hours, the ultrasonic working frequency is 40kHz, let it stand for 30 minutes, pour out the supernatant; then add 220ml of mixed acid, add Heat to 75°C, stir for 4 hours, ultrasonic working frequency is 40kHz, stand for 30 minutes, pour out the supernatant, wash with water to neutrality, filter and dry, remove non-graphite gangue minerals with naked eyes, place in reactor, add 90ml mixed acid to the sample bottle, pump the vacuum to -0.07Mpa, maintain for 25 minutes, then turn off the vacuum pump, open the valve of the injection bottle, use the pressure difference to make the mixed acid flow into the reactor, close the valve of the injection bottle, stir evenly, apply pressure to 0.07Mpa, heat to 65°C, stir for 3.5 hours to obtain a mixed solution. Wash the mixed solution with water to neutrality, filter and dry, and obtain 23.09g of high-purity flake graphite, with a fixed carbon content of 99.39% in the graphite product.

[0021] The graphite product was sieved through 100 mesh, 200 mesh and 325 mesh standard sieves for 15 minutes in turn. It was measured that the +100 mesh flake graphite in the graphite ore accounted for 3.85%, the -100 mesh + 200 mesh flake graphite accounted for 27.50%, the -200 mesh + 325 mesh flake graphite accounted for 30.88%, and the -325 mesh flake graphite accounted for 37.77%.

[0022] Comparative Example 2: The same flake graphite mine in Heilongjiang was selected, the fixed carbon content of graphite was 7.85%, and the main gangue minerals were quartz, feldspar, mica, calcite, kyanite, pyrite, and amphibole. The graphite ore was put into an oven for drying, weighed 256.5g, put into a high-temperature resistance furnace with nitrogen, heated to 650℃, calcined for 9 minutes, taken out and quickly immersed in water, taken out and hammered to less than 6 mm, put into a polytetrafluoroethylene beaker after oven drying, placed in a ventilated place, added 800ml of mixed acid (hydrofluoric acid: hydrochloric acid: nitric acid = 3:2:2), heated to 70℃, stirred for 5h, let stand for 30 minutes and pour out the supernatant; then add 600ml The mixed acid was heated to 70°C, stirred for 3 hours, and allowed to stand for 30 minutes, and the supernatant was poured out; then 500 ml of the mixed acid was added, heated to 70°C, stirred for 3 hours, and allowed to stand for 30 minutes, and the supernatant was poured out. Then the lower mixed liquid was sieved, and large particles of gangue minerals were removed with the naked eye to obtain 25.56 g of graphite product with a fixed carbon content of 77.86%. After sieving with a 100-mesh standard sieve for 15 minutes, it was measured that the +100-mesh product accounted for 6.32% of the graphite product. Example

[0023] The flake graphite ore produced in Tanzania was selected, with a fixed carbon content of 8.65% and main gangue minerals of quartz, feldspar, kaolinite, mica and limonite. The graphite ore was put into an oven for drying, weighing 235.78g, and crushed to 4.5 mm by a crusher.

[0024] Then put the crushed graphite ore into a polytetrafluoroethylene beaker, place it in a ventilated place, and add 500 ml of mixed acid, which is a mixture of hydrofluoric acid, hydrochloric acid and nitric acid in a volume ratio of 4:3:1.

[0025] At room temperature and pressure, let it stand and soak for 24 hours, remove the supernatant; then add 450ml of mixed acid, let it stand and soak for 24 hours at room temperature and pressure, remove the supernatant; then add 300ml of mixed acid, let it stand and soak for 24 hours at room temperature and pressure, wash the lower mixed liquid with water until it is neutral, filter and dry, place it in an ultrasonic device, add 260ml of mixed acid, heat to 50℃, stir for 4.5h, the ultrasonic working frequency is 40kHz, let it stand for 30 minutes, pour out the supernatant; then add 200ml of mixed acid, heat to 6 0℃, stirred for 5h, the ultrasonic working frequency was 40kHz, and the supernatant was poured out for 30 minutes, washed with water until neutral, filtered, and dried. After removing large particles of gangue minerals with naked eyes, it was placed in a reactor, 65ml of mixed acid was added to the sample bottle, and the vacuum degree was pumped to -0.08Mpa. After maintaining for 40 minutes, the vacuum pump was turned off, the valve of the injection bottle was opened, and the mixed acid was flowed into the reactor by pressure difference. The valve of the injection bottle was closed, and after stirring evenly, the pressure was applied to 0.06Mpa, heated to 60℃, and stirred for 4h to obtain a mixed solution. The mixed solution was washed with water until neutral, filtered, and dried to obtain 20.15g of high-purity flake graphite, and the fixed carbon content of the graphite product was 99.16%.

[0026] The graphite product was sieved through 30 mesh, 50 mesh, 80 mesh, 100 mesh and 200 mesh standard sieves for 15 minutes in turn. It was measured that the +30 mesh flake graphite in the graphite ore accounted for 2.57%, the -30 mesh + 50 mesh flake graphite accounted for 45.32%, the -50 mesh + 80 mesh flake graphite accounted for 21.36%, the -80 mesh + 100 mesh flake graphite accounted for 10.55%, the -100 mesh + 200 mesh flake graphite accounted for 12.32%, and the -200 mesh flake graphite accounted for 7.88%.

[0027] Comparative Example 3: The same flake graphite mine in Tanzania was selected, the fixed carbon content of graphite was 8.65%, and the main gangue minerals were quartz, kaolinite, feldspar, mica, and hematite. The graphite ore was put into an oven for drying, weighed 230.55g, put into a high-temperature resistance furnace with nitrogen, heated to 660°C, calcined for 8 minutes, taken out and quickly immersed in water, taken out and hammered to less than 6 mm, put into a polytetrafluoroethylene beaker after oven drying, placed in a ventilated place, added 600ml of mixed acid (hydrofluoric acid: hydrochloric acid: nitric acid = 4:3:1), heated to 65°C, stirred for 4h, let stand for 30 minutes and pour out the supernatant; then add 450ml of mixed acid, heated to 70 ℃, stir for 3h, let stand for 30 minutes and pour out the supernatant; then add 300ml of mixed acid, heat to 70 ℃, stir for 3h, let stand for 30 minutes and pour out the supernatant, then wash the lower mixed liquid with water until neutral, filter and dry, remove large particles of gangue minerals with the naked eye, and obtain 22.97g of graphite product with a fixed carbon content of 85.83%. After sieving with a 100-mesh standard sieve for 15 minutes, it was measured that the +100-mesh product accounted for 80.93% of the graphite product.

Claims

1. A method for determining the particle size of graphite in flake graphite ore, characterized in that: The following steps are involved: (1) Select graphite ore and put it into an oven for drying; (2) Using a crusher to break the dried graphite ore into particles smaller than 6 mm; (3) subjecting the crushed graphite ore to static acid leaching treatment; In step (3), the specific process of the static acid leaching treatment is: placing the crushed graphite ore into a polytetrafluoroethylene beaker, adding a mixed acid, standing and soaking for 24 hours at room temperature and pressure, removing the upper clear liquid, and repeating 2 to 4 times; (4) Wash the graphite ore after static acid leaching until it is neutral, filter it and dry it, and then perform ultrasonic acid leaching treatment; In step (4), the specific process of the ultrasonic acid leaching treatment is: washing the graphite ore after room temperature acid leaching until it is neutral, filtering, and drying, placing it in a stainless steel ultrasonic device coated with polytetrafluoroethylene with heating and stirring functions, adding mixed acid, stirring at 40-80°C for 2-6 hours, standing and settling, removing the upper clear liquid, and repeating 1-4 times; (5) Wash the graphite ore after ultrasonic acid leaching to neutrality and dry it, and then perform vacuum leaching followed by pressurized acid leaching; In step (5), the specific process of the vacuum-first followed by pressurized acid leaching treatment is as follows: the graphite ore after ultrasonic acid leaching is washed with water until it is neutral and dried, large particles of gangue minerals are visually searched and removed, and then the graphite ore is placed in a device under a vacuum degree of -0.06 to -0.08 MPa, mixed acid is added, stirred evenly, heated to 45 to 70°C under a pressure of 0.04 to 0.08 MPa, and stirred for 2 to 4 hours to obtain a mixed solution; (6) The mixed solution is washed with water until it is neutral, filtered, and dried to obtain high-purity flake graphite, which is then sieved using a standard sieve to determine the graphite particle size.

2. A method for measuring graphite particle size in flake graphite ore according to claim 1, characterized in that: The drying equipment in step (1) is an oven, and the oven is set at a temperature of 100-105°C.

3. A method for measuring graphite particle size in flake graphite ore according to claim 1, characterized in that: The mixed acid in steps (3), (4) and (5) refers to an acid solution obtained by mixing hydrofluoric acid, hydrochloric acid and nitric acid. The volume ratio of hydrofluoric acid to hydrochloric acid is (1-4): (1-3): (1-3), and the liquid-solid ratio of the mixed acid to graphite is 0.8-5.5 ml / g.

4. A method for determining the particle size of graphite in flake graphite ore according to claim 1, characterized in that: The ultrasonic operating frequency in step (4) is 28~40kHz.

5. A method for measuring graphite particle size in flake graphite ore according to claim 1, characterized in that: The equipment described in step (5) is a reactor, which is connected to a vacuum pump, a stirring device and a sample injection bottle. The inner wall of the reactor and the stirring device are both made of polytetrafluoroethylene material. The graphite ore dried after ultrasonic acid leaching is placed in the reactor, and the mixed acid solution is added to the sample injection bottle. Before adding the mixed acid, the graphite ore needs to be placed in a vacuum degree of -0.06~-0.08MPa for 10~50min.

Citation Information

Patent Citations

  • Method for purifying high-purity graphite

    CN101973545A

  • High stability graphite purification method

    CN104340967A

  • Method for determining content of large flaky graphite in flaky graphite ore

    CN105823712A

  • Method for detecting grain distribution characters of flaky graphite

    CN107462452A

  • Purification method for mixed acid leaching-ultrasonic water washing of spherical graphite

    CN115716645A